Retrospective cohort evaluation study in terms of cardiovascular and metabolic diseases in chronic hepatitis B patients - Yakut, Aysun (Frontiers in Endocrinology, 2024)
Background:Chronic hepatitis B (CHB) and nucleotide analogues (entecavir (ETV) and tenofovir disoproxil fumarate (TDF)) used in its treatment have been shown to affect metabolic parameters in many studies. In this study, we aimed to investigate the effects of metabolic events associated with CHB and nucleotide analogues (NAs) used in CHB treatment on ischemic heart diseases (IHD) and cardiovascular diseases (CVD).Methods:This retrospective study was conducted between June 2022 and January 2024 with a total of 241 patients diagnosed with non-cirrhotic CHB in the gastroenterology outpatient clinic, 96 of whom did not receive hepatitis B treatment, 110 of whom received TDF, and 35 of whom received ETV treatment. Patients were evaluated in terms of metabolic, CVD, and hepatology depending on whether they received antiviral treatment or not. In our study, the triglyceride-glucose (TyG) index and triglyceride-to-high-density lipoprotein cholesterol ratio (TG/HDL-C) were calculated in patients to evaluate potential risk factors for CVD. Again, while the total cholesterol-to-HDL-C ratio (TC/HDL-C), which is associated with CVD\IHD, was evaluated, the '4-factor fibrosis index' (FIB-4) score, which is a non-invasive indicator of liver fibrosis, was also evaluated.Results:Diabetes mellitus (DM), fasting blood sugar (FBS), oral antidiabetic drug (OAD) usage rate, and insulin usage rate were high in patients receiving ETV treatment. The TyG index of patients receiving ETV was higher than patients in the other group (p = 0.035; p<0.05). It was determined that the probability of detecting ETV treatment in patients with a TG/HDL-C ratio of ≥1.82 cut-off value was 4.250 times higher. The odds ratio for TG/HDL-C measurements was 4.250 (95% CI:1.384–13.054). FIB-4 score, which is a non-invasive indicator of liver fibrosis, was found to be higher in patients receiving ETV than in other groups.Conclusion:In patients with CHB, a relationship was observed between markers used to predict CVD risk, such as the TyG index and TG/HDL-C ratio. The group with high levels of these two markers and a high potential for developing CVD was patients receiving ETV treatment. In this first study in the literature showing the relationship between CHB and CVD, we found that the relative risk of CVD was increased in patients using ETV.